Platelet reactivity is higher in e-cigarette vaping as compared to traditional smoking. (15th November 2021) - Metzen, Daniel; M'Pembele, René; Zako, Saif; Mourikis, Philipp; Helten, Carolin; Zikeli, Dorothee; Ahlbrecht, Samantha; Ignatov, Denis; Ayhan, Aysel; Huhn, Ragnar; Zeus, Tobias; Levkau, Bodo; et al.
Abstract: Introduction: Vaping emerges as alternative to standard tobacco smoking. However, there is evidence for critical cardiovascular, gastrointestinal and respiratory side effects. Nevertheless, long-term vaping effects on thrombocyte reactivity have not been investigated. Therefore, we investigated the influence of vaping on thrombocyte reactivity in comparison to standard smoking and non-smoking. Methods: Platelet function was measured by Multiplate Impedance Aggregometry as area under the curve (AUC). Smoking habits and characteristics were assessed by questionnaire. Results were analyzed using inverse probability of treatment weighting (IPTW) and conventional t -tests to test for robustness. Results: After IPTW adjustment, participants in all groups were balanced by age, gender, body height and weight. Collagen-induced aggregation was higher in vapers compared to non-smokers (non-smokers 52.55 ± 23.97 vs. vapers 66.63 ± 18.96 AUC, p  = 0.002) and to smokers (vapers vs. smokers 49.50 ± 26.05 AUC, p  < 0.0001). ADP-induced aggregation in vapers was higher compared to non-smokers (non-smokers 33.16 ± 16.61 vs. vapers 45.27 ± 18.67 AUC, p  = 0.001) and was numerically increased compared to smokers (vapers vs. smokers 40.09 ± 19.80 AUC, p  = 0.08). These findings remained robust in t -test analysis. Conclusion: This study provides first evidence that vaping leads to enhanced platelet reactivity compared to standard smoking and non-smoking. This suggests health effects of vaping might be more severe than previously assumed. Whether this effect translates to clinical outcome with a higher incidence of major cardiovascular events, should be evaluated in large-scaled clinical studies. Highlights: E-cigarettes have become a common form of nicotine consumption. Recent studies observed augmented pathologies similar to traditional smoking. Enhanced platelet reactivity in traditional smoking increases ischemic events. Chronic vaping is associated with higher platelet reactivity as compared to traditional smoking and non-smoking. This finding suggests that health effects of vaping might be more severe than previously assumed.